Subgradient method with feasible inexact projections for constrained convex optimization problems. (2nd December 2022) - Aguiar, A. A.; Ferreira, O. P.; Prudente, L. F.
Abstract : In this paper, we propose a new inexact version of the projected subgradient method to solve nondifferentiable constrained convex optimization problems. The method combine ϵ -subgradient method with a procedure to obtain a feasible inexact projection onto the constraint set. Asymptotic convergence results and iteration-complexity bounds for the sequence generated by the method employing the well-known exogenous stepsizes, Polyak's stepsizes, and dynamic stepsizes are established.